Mitochondria: a crucial factor in the progression and drug resistance of colorectal cancer - Zhao, Ying; Guo, Xiaomin; Zhang, Li; Wang, Dongwei; Li, Yan (Frontiers in Immunology, 2024)
Colorectal cancer (CRC), as one of the malignant tumors with the highest incidence and mortality rates worldwide in recent years, originating primarily from the mucosal tissues of the colon or rectum, and has the potential to rapidly develop into invasive cancer. Its pathogenesis is complex, involving a multitude of factors including genetic background, lifestyle, and dietary habits. Early detection and treatment are key to improving survival rates for patients with CRC. However, the pervasive problem is that patients can become severely resistant to treatment, which greatly increases the complexity and challenge of treatment. Therefore, unraveling and overcoming the resistance of CRC has become a focus of research. Mitochondria, the energy centers of the cell, play a crucial role in cellular metabolism, energy supply, and the apoptosis process. In CRC, Mitochondrial dysfunction not only impairs normal cell function but also promotes tumor resistance. Therefore, a deep understanding of the relationship between mitochondrial dysfunction and the mechanisms of CRC development, as well as the mechanisms by which it promotes resistance to chemotherapy drugs, is crucial for the development of targeted therapies, enhancing drug efficacy, and improving treatment outcomes and quality of life for patients.